Probiotic lactic acid bacteria in biotechnology and the food industry: A review - Damla Avci; Simona Gillarová; Svatopluk Henke; Zdeněk Bubník; Marcela Sluková (Czech Journal of Food Sciences)
This review explores the diverse applications and health benefits of probiotic lactic acid bacteria (LAB) through biotechnological applications in the food industry. While all LAB are indispensable for the production of fermented foods thanks to their ability to produce lactic acid and bacteriocins that act as natural preservatives, specific strains of probiotic LAB offer targeted health benefits. In addition to general benefits of LAB, probiotic strains significantly enhance gut microbiota, enhance human immunity, and exhibit antimicrobial properties. This review also delves into the mechanisms of action of probiotic LAB, focusing on adhesion, colonisation, and antioxidant production, emphasising their potential to advance nutritional innovations. Beyond food production, the broader category of LAB has transformative potential in industrial applications, particularly in the sugar industry, where their metabolic activity can improve sucrose extraction processes, promote microbial management, and reduce unwanted by-products. By understanding these aspects, the review underscores the importance of probiotic LAB in promoting health, efficiency, and sustainability across sectors.